Educação ambiental em projetos político pedagógicos de escolas públicas estaduais em Rondonópolis-MT : construção discursiva no percurso da transversalidade - Costa, Cristiane Araújo (2022)
The research entitled Environmental Education in Political-Pedagogical Projects of State Public Schools in Rondonópolis-MT: discursive construction in the course of transversality was motivated by the problematizations to be made regarding the environmental crisis in the world context and the destructive and inconsequential behavior of human beings towards the nature. The proposal has Environmental Education as its object of study, delimiting the development of research to the analysis of proposals or planning in teaching regarding environmental education and the way in which it is presented in the Political-Pedagogical Projects examined for the various subjects of Elementary School in the period 2020 annual school year. For its construction, we chose to follow the paths of Qualitative Research, using the Discourse Analysis in the Pecheutiana Perspective as an instrument. The research has as general objective to investigate the presence of foundations and elements of Environmental Education and its transversality in Political-Pedagogical Projects for elementary education, in four state public schools in the city of Rondonópolis. The readings and analyzes obtained as results answers related to the specific objectives of this research: The Pedagogical Political Projects were built in accordance with the norms of the National Common Curricular Base, with Environmental Education, as a public policy, present in projects and schools in different conceptions and situations; in the school community, in the midst of a heterogeneous public, Environmental Education manifests itself in the most diverse conceptions of work and in its political practice. The Pecheutiana Discursive Analysis revealed in the movements of meanings that the collaborating schools, from their place of speech, direct their projects for the construction of collective interests, instituting affirmative, political and anti-hegemonic actions.